Rhinofilling with hyaluronic acid thought as a cartilage graft. Issue 3 (March 2020) - Rauso, Raffaele; Tartaro, Gianpaolo; Chirico, Fabrizio; Zerbinati, Nicola; Albani, Giada; Rugge, Luigi
Abstract: Introduction: There is great demand for nonsurgical aesthetic procedures. In this case series, the authors describe their stepwise technique of injecting hyaluronic acid (HA) into the nose to yield pleasing, stable results. Case series: A total of 148 patients underwent minimally invasive rhinoplasty by injection of HA filler. Anatomic contraindications for the procedure were a large dorsal hump, extreme tip projection, or excessive nasal deviation. HA injections were made in a specific order to reshape and stabilize the nose; the surgical plan was conceptually similar to placement of cartilage grafts. Patients indicated their satisfaction with the surgical results on a visual analog scale. Immediately after the procedure, all patients had transient redness and slight swelling at the injection site; this resolved spontaneously by 24 h posttreatment. Vascular impairment developed in 1 patient and was managed with hyaluronidase. In general, patients expressed a high level of satisfaction. Thirty-two patients returned for a "touch-up" filler injection 1 year posttreatment. Discussion: Nasal reshaping by HA injection can be carried out quickly, safely, and effectively with minimal patient discomfort or downtime. Care must be given to select patients who are indicated for this procedure, and meticulous pretreatment planning is necessary.